Strengthening Digital-Based Youth Organizational Leadership to Revitalize Community Participation in Mejoyo Village, Mojokerto - Faiqotul Isma Dwi Utami; Rinda; Shafaatul Khikma; Mochamad Nur Najmal Falach (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
Youth organizations hold potential as transformative agents within community governance, especially in rural settings where traditional modes of participation are being reshaped by digital technologies. This study aimed to enhance digital-based leadership among youth organizations in Mejoyo Village, Mojokerto Regency, addressing organizational stagnation and diminished civic engagement. Using participatory action methodology, researchers implemented leadership workshops, digital communication training, and collaborative engagements with village authorities. Quantitative and qualitative data were gathered via focus group discussions, structured observations, and reflective questionnaires. Findings revealed increases in leadership competencies, organizational initiative, and youth-led community projects. The study highlights that digital leadership capacity building fosters sustainable youth participation, strengthens intergenerational collaboration, and contributes to vibrant community governance. These insights have implications for designing youth empowerment programs that integrate digital competencies with community development frameworks